2018
DOI: 10.3390/rs10111672
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Identification of Remnant PFM-1 ‘Butterfly Mines’ with a UAV-Based Thermal-Imaging Protocol

Abstract: Use of landmines as a weapon of unconventional warfare rapidly increased in armed conflicts of the last century and some estimates suggest that least 100 million remain in place across post-conflict nations. Among munitions and explosives of concern (MECs), aerially deployed plastic anti-personnel mines are particularly challenging in terms of their detection and subsequent disposal. Detection and identification of MECs largely relies on the geophysical principles of magnetometry and electromagnetic-induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
(51 reference statements)
1
15
0
Order By: Relevance
“…(2) Can Faster R-CNN be used to automate the detection and map the coordinates of these mines? Previous research has demonstrated the efficacy of thermal imaging to detect the PFM-1 in static and active field trials [10][11][12]. This study expands upon those results by demonstrating the ability of a low-cost plug-and-play multispectral sensor to detect scatterable surface-laid antipersonnel landmines in the visible light, green, red, red-edge, and near-infrared bands of the electromagnetic spectrum.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…(2) Can Faster R-CNN be used to automate the detection and map the coordinates of these mines? Previous research has demonstrated the efficacy of thermal imaging to detect the PFM-1 in static and active field trials [10][11][12]. This study expands upon those results by demonstrating the ability of a low-cost plug-and-play multispectral sensor to detect scatterable surface-laid antipersonnel landmines in the visible light, green, red, red-edge, and near-infrared bands of the electromagnetic spectrum.…”
Section: Discussionsupporting
confidence: 66%
“…Following the stationary proof-of-concept phase, we deployed an unmanned aerial vehicle (UAV) with a mounted infrared camera to remotely collect automated time-lapse thermal surveys over simulated minefields seeded with inert PFM-1 mines and aluminum elements of the KSF-1 casing. Dynamic UAV datasets confirmed that PFM-1 mines yielded statistically significant (and remotely detectable) temperature differences between the polyethylene bodies of the landmines and their host environments, both in direct thermal comparisons and in time-lapse DATI datasets [11].…”
Section: Landmine Overviewmentioning
confidence: 62%
See 1 more Smart Citation
“…Remotely piloted aircraft systems (RPAS) provide special advantages over other platforms, in particular high GSD, and more economical preparations for performing and collecting data in smaller areas. Examples of RPAS use in landmine detection can be found in [37][38][39], and indicators of mine presence detection in [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The authors thank the Urs Endress foundation for supporting this work. https://www.ue-stiftung.org as "butterfly mine" [2] which has been used extensively in Afghanistan. This mine exhibits an elongated aluminium cylinder in the center surrounded by an explosive filled plastic cover in the form of a butterfly wing.…”
Section: Introductionmentioning
confidence: 99%